PENGARUH MOTIVASI KERJA, KEPUASAN KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI BAGIAN KEUANGAN PADA PEMERINTAH DAERAH (Studi pada Dinas Pendapatan Keuangan dan Aset Daerah Kabupaten Natuna) - Tetty Mawarni; Andreas '; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the effect of work motivation, job satisfaction and compensation on employee performance in the Finance Section DPKAD Natuna regency. The collection of data with the primary data using questionnaires. Samples in this study were 44 employees in the finance department DPKAD Natuna regency with the sampling technique used is to use the full sample. Processing and analysis of data by multiple regression analysis using SPSS version 17. The results showed that the work motivation, job satisfaction and compensation influence on employee performance. While the value of R2 that is equal to 0.931, which means 93.2% of independent variables affect the dependent variable, while the remaining 6.9% is influenced by other variables not examined in this study.Keywords: Work Motivation, Job Satisfaction, Compensation and Employee Performance